Electronic structure peculiarities of disordered Mn and Co diphosphates - Karbivskyy, V.L.; Smolyak, S.S.; Zagorodniy, Yu.A.; Kasiyanenko, V.H. (Functional Materials, 2012)
Electronic structure peculiarities of disordered diphosphate —Mn₂₋ₓCoₓP₂O₇*5H₂O, with x = 0, 0.6, 1.0, 1.9, 2.0, were studied by XPS and X-ray emission spectroscopy. Substitution in the different degree of cobalt by manganese leads to a charge redistribu¬tion in the metal sublattice and results in increase of the chemical bond ionicity between oxygen anions and the metal cations. Such charge redistribution is responsible for forma¬tion of the states laying in the upper part of the valence band.